Efficacy of certain therapeutic regimens in canine pyometra - KHAN, L A; RAGHUWANSHI, D S; VOHRA, S C; UTAGE, S G (The Indian Journal of Animal Reproduction, 2007)
Pyometra in dogs is life threatening disorder. Though the hysterectomy is the treatment of choice but itceased the future fertility permanently. Thus for the prevention of future fertility comparative efficacy of differenttherapeutic regimens was studied in 24 confirmed pyometra bitches. The bitches were divided into four groups,each group consisting of six bitches. Group I bitches were treated with cloprostenol + intramuscular antibioticsand recorded 83.33% efficacy of the treatment. Group II bitches were treated with cloprostenol + intrauterineantibiotics with an efficacy of 83.33%. Group III bitches were treated with cloprostenol + intramuscular antibiotic+ povidone iodine intrauterine and all the six bitches cured completely, indicating I 00% efficacy of the treatment.Whereas, bitches in grovp IV were treated with intramuscular antibiotic + povidone iodine intrauterine andrecorded 66.66% efficacy of the treatment. Bitches treated with cloprostenol + intramuscular antibiotics +povidone iodine intrauterine, recorded good and appreciable response than other treatment.
Keywords: Canine; Pyometra; Cloprostenol; Intrauterine medication; Ultrasound